1982
DOI: 10.1007/bf02774761
|View full text |Cite
|
Sign up to set email alerts
|

Gastric acid secretion, serum gastrin and parietal cell histology in rat hyperthyroidism

Abstract: Experimental hyperthyroidism was produced in rats by thyroxin injection, and changes in gastric acid secretion and serum gastrin level were determined to analyze the relation between these changes and hyperthyroidism. Administration of thyroxin to two groups of rats-20 micrograms per 100 g of body weight for 20 days and 75 micrograms for 7 days-brought about significant increases in serum T3 level, gastric pH and serum gastrin level. An increase in gastric pH took place later than that in serum T3 level; this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The relationship between thyroid hormones and its altered states on gastric acid secretion has been studied in several animal species and human (Akiyama et al, 1982;Kazuhiko et al, 2006). The reduced secretion in carbimazole treatment and increased secretion in tyrosine treatment is in agreement with the studies on rats (Akiyama et al, 1982;Adeniyi and Olowookorun, 1990); in human subjects (Kazuhiko et al, 2006;Fatemeh and Saleh, 2012). Adeniyi and Olowookorun (1990) suggested that thyroid hormones regulate basal and secretagogue stimulated acid secretion via their effects on parietal cell mass (Adeniyi and Olowookorun, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between thyroid hormones and its altered states on gastric acid secretion has been studied in several animal species and human (Akiyama et al, 1982;Kazuhiko et al, 2006). The reduced secretion in carbimazole treatment and increased secretion in tyrosine treatment is in agreement with the studies on rats (Akiyama et al, 1982;Adeniyi and Olowookorun, 1990); in human subjects (Kazuhiko et al, 2006;Fatemeh and Saleh, 2012). Adeniyi and Olowookorun (1990) suggested that thyroid hormones regulate basal and secretagogue stimulated acid secretion via their effects on parietal cell mass (Adeniyi and Olowookorun, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that they also affect gastric acid secretion . Akiyama et al (1982) found out that the administration of thyroxine into rats led to significant increases in serum T 3 level, gastric pH (reduced acid secretion) and serum gastrin level. Adeniyi and Olowookorun observed that chronic administration of thyroxine increased parietal cell mass, as well as basal acid secretion and histamine-stimulated acid secretion (Adeniyi and Olowookorun, 1989), mice also show the same trend (Olaleye and Elegbe, 2005).…”
Section: Introductionmentioning
confidence: 99%